The Use of Euphemism in Acehnese Ethnic Language - Husna, Asmaul; Khodijah, Siti (EXCELLENCE: Journal of English and English Education, 2024)
Language is very important in human society to communicate with another people in everyday life; the understanding of language in communication becomes very important according to the main purpose of language which can be associated as a medium for delivering a massage or information. There are several words or phrases of dysphemism or taboo word in the culture of a society which then allows the emergence term to smooth the language, it’s called by euphemism. In each ethnic language has dysphemism and euphemism, such as Acehnese ethnic language. This article is to describe the use, the type and the function of euphemism in Acehnese ethnic language. The method used is descriptive qualitative. The data of this research were the words and phrases containing euphemism. The source of the data was taken from interviewees some Acehnese speaker by sending message and recording the dialog used by Acehnese speaker which use euphemism. From the data analyzed, the euphemism is mostly appeared as the function as tools for smooth speech. In this culture is only found some types of euphemism. They are jargon type used in pronoun and noun, second flippancy type used in adjective and verb and the last colloquial type used in phrase. In Acehnese language people tend  to use of euphemism as consideration to adapt speech in different addressee and situation, and show respect and politeness each other.